2024
DOI: 10.1101/2024.03.20.586010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioorthogonal labeling and enrichment of histone monoaminylation reveal its accumulation and regulatory function in cancer cell chromatin

Nan Zhang,
Jinghua Wu,
Farzana Hossain
et al.

Abstract: Histone monoaminylation (i.e., serotonylation and dopaminylation) is an emerging category of epigenetic mark occurring on the fifth glutamine (Q5) residue of H3 N-terminal tail, which plays significant roles in gene transcription. Current analysis of histone monoaminylation is mainly based on site-specific antibodies and mass spectrometry, which either lacks high resolution or is time-consuming. In this study, we report the development of chemical probes for bioorthogonal labeling and enrichment of histone ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…1A) was synthesized (Supplementary Information) and characterized, based on the protocols reported in our previous study. 13 HCT116 cells were cultured and utilized as a model of colorectal cancer to identify dopaminylated proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A) was synthesized (Supplementary Information) and characterized, based on the protocols reported in our previous study. 13 HCT116 cells were cultured and utilized as a model of colorectal cancer to identify dopaminylated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…13 Utilizing this chemical biology tool, we found that histone dopaminylation was accumulated in tumor cells that overexpress TGM2 (e.g., colon and breast cancer cells). 13 In this research, we applied this BCN-biotin probe to modify the dopaminylated proteome in colorectal cancer (HCT116) cells via the biorthogonal reaction, SPOCQ. Therefore, 425 dopaminylated proteins were significantly enriched and identified from the experimental group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations